Expression of inflammatory mediators in periodontitis and T2D patients: a systematic review and meta-analysis - Mariana Caldas de Oliveira MATTOS; Laís Garreto Alves de Almeida CHAGAS; Cristine Miron STEFANI; Nailê DAMÉ-TEIXEIRA; Daniela Correa GRISI; Loise Pedrosa SALLES; Laudimar Alves de OLIVEIRA; Valéria Martins de Araújo CARNEIRO; Maria do Carmo Machado GUIMARÃES (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract The high concentration of glucose in the blood in Type 2 diabetes (T2D) may be related to either insulin resistance or insulin deficiency. Moreover, the literature points to periodontitis as the main oral disease caused by glycemia imbalance. The quantification of inflammatory markers in blood or saliva samples of T2D patients may represent a valuable tool in revealing how well an individual's immune system can respond to injuries and periodontal treatment. In addition, an evaluation of the cytokine expression is extremely relevant to help understand the connection between periodontitis and T2D. This systematic review and meta-analysis aimed to evaluate the expression of inflammatory markers in T2D patients with periodontitis, compared with non-diabetic patients with periodontitis. A total of 3,894 studies were retrieved after a systematic literature search, 15 of which were included in the systematic review, and 4 of these 15, in the meta-analysis. The results did not indicate any statistical difference between the groups regarding TNF-α and IL-6 markers. T2D patients with periodontitis had increased levels of IL-10, compared with non-diabetic individuals with periodontitis (p = 0.003). On the other hand, the IL-4 concentration in non-diabetic individuals with periodontitis was high, compared with the T2D group (p< 0.001). Several studies did not include quantitative results and were excluded from the meta-analysis. The high IL-10 expression and low IL-4 expression in the T2D group suggest an association between the level of these markers and the impairment of the immune response in T2D patients with periodontitis.